New and little-known Eugryllacris from Yunnan, China (Orthoptera: Gryllacrididae: Gryllacridinae) - Yin, Zi-Xu; Shen, Si-Zhong (Zootaxa, 2021)
Eugryllacris species from Yunnan, China were investigated from 2018 2021. A new species, Eugryllacris tiga sp. nov. is described from China. The male morphology and ecology of E. cf. vaginalis Pictet & Saussure, 1893 and E. guomashan Ingrisch, 2018 are illustrated for the first time. The type species are deposited in Museum of Biology, East China Normal University (ECNU).